1974
DOI: 10.1161/01.cir.49.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Ventriculo-Atrial Conduction in the Wolff-Parkinson-White Syndrome

Abstract: SUMMARYIn 36 patients with the Wolff-Parkinson-White syndrome, ventriculo-atrial (VA) conduction was studied using the single test stimulus method. In 22 patients no significant change in VA conduction time occurred following test stimuli with increasing prematurity suggesting exclusive VA conduction by way of the accessory pathway, an accessory pathway with a shorter refractory period than the His-AV node pathway, or identical refractory periods in both pathways. In 14 patients showing this VA conduction patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(13 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…Klein et al14 recently observed decremental retrograde conduction via anomalous bypass tracts in three of their 30 patients with the Wolff-Parkinson-White syndrome. However, the magnitude of conduction delay during retrograde conduction over the slow pathway as demonstrated in this study was much greater than that reported by Klein et al, 1 as evidenced by recordings of atrial electrograms far apart from those of ventricular electrograms during retrograde slow pathway conduction (ventriculoatrial -intervals ranged from 290-525 msec) (figs. [4][5][6].…”
Section: Resultscontrasting
confidence: 63%
“…Klein et al14 recently observed decremental retrograde conduction via anomalous bypass tracts in three of their 30 patients with the Wolff-Parkinson-White syndrome. However, the magnitude of conduction delay during retrograde conduction over the slow pathway as demonstrated in this study was much greater than that reported by Klein et al, 1 as evidenced by recordings of atrial electrograms far apart from those of ventricular electrograms during retrograde slow pathway conduction (ventriculoatrial -intervals ranged from 290-525 msec) (figs. [4][5][6].…”
Section: Resultscontrasting
confidence: 63%
“…2a) (Narula, 1974;Wellens and Durrer, 1974). The small but equal increase in V-RA and V-LA intervals in 1 patient was attributed to intraventricular delay.…”
Section: Resultsmentioning
confidence: 99%
“…The use of retrograde atrial sequence and of functional bundle-branch block has been described in detail in recent publications (Coumel and Attuel, 1974;Spurrell et al, 1974;Zipes et al, 1974;Svenson et al, 1974;Wellens and Durrer, 1974;Gallagher et al, 1975;Neuss et al, 1975;Tonkin al., 1975). The use of atrial stimulation at multiple sites has received less attention.…”
Section: Discussionmentioning
confidence: 99%